The orientational salience of visual cues to the homing pigeon - Chappell, J; Guilford, T (1997)
A potentially valuable method for investigating the role of visual landmarks in the familiar area map is to use an open-field arena food-searching task, allowing landmarks and the sun compass to be independently manipulated. In previous such experiments performed outdoors, homing pigeons, Columba livia, primarily used the sun compass rather than visual cues to locate the target goal. One possible reason for this result may have been that the artificial two-dimensional landmarks provided lacked salience, forcing the pigeons to rely on the sun compass. In this study the salience of two-dimensional visual cues indoors, where the sun compass was not available, was investigated. As pigeons were unexpectedly unable to learn this task consistently, in a second experiment a three-dimensional cue was added. The results suggest that: (1) pigeons are unable to use two-dimensional cues to locate the target goal consistently, when no other directional cues are available, but are able to use a three-dimensional cue in an otherwise identical task; (2) pigeons do not use non-visual cues (such as the magnetic compass) indoors to locate the target goal; and (3) the scatter in mean bearings often observed in clock-shifted pigeons is not caused by non-specific disturbance resulting from shifting the internal clock. The significance of our results is discussed in relation to the homing mechanisms used by pigeons at familiar sites.